2009
DOI: 10.1007/s10209-009-0148-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding users and their needs

Abstract: Gaze-control enables people to control a computer by using eye-gaze to select items on screen. Gazecontrol is a necessity for people who have lost all motor control of their body and only have control over eye movements. In addition, gaze-control can be the quickest and least tiring option for a far broader group of people with varying disabilities. This paper reports findings from gaze-control user trials involving users from both groups: people who are totally paralyzed, as well as people with a wide range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…Goossens (1989) proposed that eye gaze is a natural response mode and precedes the verbal response mode; eye gaze also may be easier, quicker, and more effective than other testing accommodations, especially for people with physical disabilities (Donegan et al 2009). Casey et al (2007) suggested that under cognitively demanding conditions (for example, test taking), learners revert to a previous and more immature level of response mode in order to accurately respond to questions.…”
Section: Discussionmentioning
confidence: 99%
“…Goossens (1989) proposed that eye gaze is a natural response mode and precedes the verbal response mode; eye gaze also may be easier, quicker, and more effective than other testing accommodations, especially for people with physical disabilities (Donegan et al 2009). Casey et al (2007) suggested that under cognitively demanding conditions (for example, test taking), learners revert to a previous and more immature level of response mode in order to accurately respond to questions.…”
Section: Discussionmentioning
confidence: 99%
“…Eye gaze technologies may appear intuitively easy to use, but in fact they are both cognitively and visually complex [13], relying on consistent control of eye movements, as well as the ability to switch between using gaze to explore a screen to selecting a cell or item on that screen [30]. Mastering these skills takes time (up to at least 20 months by one estimate [31]), can involve considerable physical and cognitive effort, but can be motivating and perceived to be well worth that effort [32]. Researchers are still at the early stage of evaluating how best to organize items on a visual display to maximize ease of access for each individual [33], and how best to provide user feedback to support learning [34].…”
Section: Innovations In Input/access Methodsmentioning
confidence: 99%
“…Although eye gaze technology was initially mainly used for people who were literate and cognitively able, advances in this technology have enabled its application to persons with more diverse abilities, including preliterate children [1]. Messages on electronic AAC systems for preliterate children are typically encoded using pictorial (also called graphic) symbol systems such as Picture Communication Symbols (PCS), SybolStix or Widgit.…”
Section: Introductionmentioning
confidence: 99%